External sector report - International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2020)
​The External Sector Report analyzes global external developments and provides multilaterally consistent assessments of external positions of the world’s largest economies, representing over 90 percent of global GDP. The report includes: (i) an overview chapter that emphasizes multilateral issues, showing how individual economies fit into the global picture and discussing associated risks and policies needed to reduce excess imbalances; (ii) an analytical chapter that covers topics relevant to the analysis of external sector dynamics and adjustment mechanisms; and (ii) a final chapter that provides details of the external assessment of each of the 30 economies considered. The External Sector Report, produced annually since 2012, is a key part of the IMF’s surveillance. External assessments are arrived at by integrating multilateral and country-specific perspectives, while ensuring individual economy assessments add up to a coherent, multilaterally consistent view. Specifically, staff assessments draw on estimates from the External Balance Assessment approach as well as country-specific evidence and judgment, while acknowledging the uncertainties inherent in such assessment" (IMF page)
Began in 2012, published once a year, and Available four issues in a library (2020, 2021, 2022, 2025) Some issues also have thematic titles.​
Includes bibliographical references.
Keywords: International Trade; INTERNATIONAL FINANCE; BALANCE OF PAYMENTS; FOREIGN INVESTMENTS; EXTERNAL DEBT; ANNUAL REPORTS